RFID TECHNOLOGY FOR SECURING E-HEALTH SYSTEM: SERVICE OF CONSULTING A DOCTOR - Yuliana, Mike; Nadhori, Isbat Uzzin; Sudarsono, Amang (European Scientific Journal, ESJ, 2014)
In this research, we propose an anonymous authentication e-health system and the use of RFID smart card that contained hidden patient’s personal identity, so the privacy of doctors and patients could improved optimally (for example, by hiding their identity). We employ Camenisch- Lysyanskaya Signature Scheme to achieve anonymity and Java programming for constructing our anonymous authentication e-health system. The results showed that the system that made have been able to protect the personal data of patient and doctor. For anonymous process, prover needs more time than the verifier, this happens because in the CL scheme, proof of knowledge is a combination of CL signatures with evidentiary value of the commit inside the CL signature value. Computational time that required for the authentication process with the smart card until accepted by the ehealth system takes 0.6 s.